Association Between Stage at Diagnosis and Knowledge on Cervical Cancer Among Patients in a Kenyan Tertiary Hospital: A Cross-sectional Study - Wamburu, Kabura; Busakhala, Naftali; Owuor, Kevin; Nyagero, Josephat (Pan African Medical Journal)
Introduction: in Kenya, cervical cancer is the second most common cancer among women; almost half of all women with invasive cervical cancer are diagnosed at a late stage. Few women are aware of the symptoms and risk factors of cervical cancer and that its precursor lesions are detectable through screening thus most women seek treatment when the cancer is at an advanced stage. The study explored the influence of cervical cancer awareness on stage at diagnosis in patients attending Kenyatta National Hospital. Methods: a cross-sectional survey was adapted to obtain socio-demographic information, knowledge on symptoms and risk factors from 361 women with histological diagnosis of cervical cancer conveniently sampled at Kenyatta National Hospital. Associations between stage at diagnosis and knowledge on cervical cancer were tested using chi-square statistic and fisher's exact test at 95% confidence interval. Results: seven in every 10 women (72.6%) presented with advanced stage cervical cancer. Knowledge on the sexually transmitted nature of cervical cancer was inadequate, 22% of women with early stage and 23.7% of women with advanced stage cervical cancer (p=0.874). Majority of the women were not aware of the causative link between cervical cancer and human papillomavirus (HPV), 8 (13.1%) of women with early stage and 5 (3.5%) of women with advanced stage cervical cancer (p=0.036). Conclusion: stage at presentation was advanced and knowledge on the role of a sexually transmitted virus in the cervical cancer aetiology was poor among the women. Increasing screening programs and providing information highlighting this association is necessary.
© Kabura Wamburu et al. The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Human papillomavirus; Cervical cancer screening; Symptoms